Port designer's handbook - Thoresen, Carl A. (Thomas Telford, 2010)
Developments in navigation safety, port planning and site selection, layout of container and oil and gas terminals, cargo handling, and fender and mooring principles are covered, plus the evaluation of operational conditions due to the impact from wind, waves and current loads on port and berth structures, and berthing and layout criteria for ships in channels and harbour basins.
Keywords: Harbors -- Design and construction.; elektronické knihy; electronic books